2011
DOI: 10.1007/s12072-010-9238-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of 48-week treatment efficacy between clevudine and entecavir in treatment-naïve patients with chronic hepatitis B

Abstract: Mean reduction of viral loads was similar between clevudine and entecavir groups during 48 weeks. However, virologic breakthrough and significant myopathy were noted only in clevudine-treated patients. Therefore, more attention should be paid to patients receiving clevudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…Similarly, our study also showed high cumulative rates of biochemical response (serum ALT <40 IU/L) (77.6% at 12 months, 86.2% at 24 months, and 86.2% at 36 months), and this was not significantly different between HBeAg-positive and negative patients. In addition, the rate of HBeAg loss or HBeAg seroconversion in our study (17.6% at 12 months, 23.5% at 24 months, and 23.5% at 36 months) was similar to previous studies (18% to 25% at week 48) 5,6,9…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, our study also showed high cumulative rates of biochemical response (serum ALT <40 IU/L) (77.6% at 12 months, 86.2% at 24 months, and 86.2% at 36 months), and this was not significantly different between HBeAg-positive and negative patients. In addition, the rate of HBeAg loss or HBeAg seroconversion in our study (17.6% at 12 months, 23.5% at 24 months, and 23.5% at 36 months) was similar to previous studies (18% to 25% at week 48) 5,6,9…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, CLV treatment led to a high frequency (78% to 84.7%) of serum ALT normalization at 48 weeks 5-9. Similarly, our study also showed high cumulative rates of biochemical response (serum ALT <40 IU/L) (77.6% at 12 months, 86.2% at 24 months, and 86.2% at 36 months), and this was not significantly different between HBeAg-positive and negative patients.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In comparison to lamivudine, clevudine seems to be superior in HBeAg positive HBV. Compared to entecavir, in chronic HBV infected patients clevudine could reduce viral load similar than entecavir, but higher rates of virological breakthrough and significantly more myopathy was observed [61] , indicating that clevudine has a higher adverse event profile.…”
Section: Main Results (S)mentioning
confidence: 99%